Joux multicollisions attack in sponge construction - AlAhmad, Mohammad A.; Alshaikhli, Imad Fakhri Taha; Nandi, Mridul (2013)
Cryptographic hash functions take an unfixed size of input and produce a fixed size of an output. A hash function usually has two main components: a compression function and mode of operation. Sponge construction is one of the main operations of modes of used in modern cryptographic hash function. In this paper, we present multicollisions attack in sponge construction. In 2004, Joux [3] presented multicollision attack in iterated hash function. Our attack is similar to Joux attack but specifically for sponge construction1. We show that finding multicollisions in sponge construction of messages that hash to the same value, is not harder finding ordinary collisions. Then, we use this attack as a tool to prove that concatenating more than one hash function in order to increase the security level does not yield to more secure construction.